In Memoriam - From the Editorial Team (Central European Public Administration Review)
Since the publication of our last issue, we have seen the passing of three esteemed members of the CEPAR community: Associate Prof. Rudi Kocjančič, PhD, and Prof. Gyorgy Jenei, PhD, former members of the CEPAR Editorial Board, and Prof. Allan Rosenbaum, PhD, a member of the CEPAR Advisory Board.